Immediate aspiration of the drug infused via central venous catheter through the distally positioned central venous dialysis catheter: An experimental study. Issue 1 (January 2021) - Vicka, Vaidas; Vickiene, Alvita; Tutkus, Jonas; Stanaitis, Jokubas; Bandzeviciute, Rimante; Ringaitiene, Donata; Vosylius, Saulius; Sipylaite, Jurate
Objectives: The aim of this study was to construct an experimental model replicating blood flow within human superior vena cava and to determine the degree of the immediate aspiration of the drug introduced via central venous catheter through the distally positioned dialysis catheter. Methods: A model replicating superior vena cava was built, catheters were inserted into the model, placing the orifice of the central venous catheter in positions regarding the orifice of the arterial lumen in central venous dialysis catheter (from +2 to −8 cm). Methylene blue was used as a tracer, and the concentration was determined by ultraviolet-visible spectroscopy. Four different sets of samples were generated according to infusion and aspiration speeds: continuous–slow, continuous–fast, bolus–slow, and bolus–fast. Results: The concentration of the tracer was related to the distance between the catheter tips, representing a bimodal dependence. When the central venous catheter was placed distally to the central venous dialysis catheter, the aspiration of the tracer was minimal. When withdrawing the central venous catheter proximally, the aspiration of the tracer increased, reaching its peak at −4 cm with aspiration rates form 4.2% to 140.7%. Furthermore, the infusion speed of the tracer had more effect on the aspirated concentrations than the aspiration speed. Conclusion: Findings of our experimental model suggest that concentration of aspired drug is effected by the distance between the central venous catheter and central venous dialysis catheter, being lowest when the drug is infused distally to central venous dialysis catheter. Furthermore, the concentration of the tracer is directly proportional to the infusion speed and far less effected by the aspiration rate of the drug.